Securing Microservices Architecture Using JSON Web Tokens (JWS) - Priyanka Gowda Ashwath Narayana Gowda (North American Journal of Engineering Research, 2023)
Microservices architecture represents the newest rage in methodologies for designing scalable and maintainable software systems.In securing these distributed services, however, decentralized architectures pose considerable challenges. This paper considersusing JSON Web Tokens to improve security in a microservices architecture. JWT offers a stateless yet compact and URL-safemeans for representing claims between two parties. Our research has targeted the structure and implementation of JWT and theintegration for authentication and authorization and has analyzed its benefits and limitations. We implemented JWT in micro-services settings to know its practical application and effectiveness for securing service-to-service communication. More recentwork was based on a case study where we compared JWT with other security mechanisms and measured their influence on per-formance. This research concludes that JWT has significantly enhanced the security of microservices and their scalability byreducing the need for a centralized authentication server and enabling stateless authentication. On the other hand, it resulted inconcerns about token size and secure key management. It is, hence, a widely acceptable concluding statement. In the future,research needs to be carried out in optimizing JWT implementation to address the limitations associated with it and additionalexploration of security features to enhance its efficacy within a complex microservices environment. Additionally, it needs to beresearched whether JWT may be combined with any other up-and-coming security protocols which may be a complete securityframework for the microservices architecture